Vite in pezzi, corpi integri. Geografie sociali della migrazione e della homelessness a Roma Termini - Silvia Antinori (Archivio Antropologico Mediterraneo)
The territory of Roma Termini, the capital’s central station, is an area innervated by a plurality of social margins “inhabited” in increasing numbers by different populations. Based on fieldwork research, this paper looks at this place from the perspective of homeless migrant people who pass through it. The people encountered embody different biographical parables yet are united by similar processes of marginalization and violence that assault bodies from multiple levels; in macroscopic terms as well as in the watermark of a daily life constituted by imposed lifetimes and forms of abandonment, deeply sedimented. It is the characteristic of chronicity of the events of suffering that marks their incorporation, that configures zones in which forms of constant dispossession and subtraction of living pieces materialize as ordinary. How to capture active practices of subjects in places where the extent of violation and incorporation of suffering is continuous? What will be attempted to bring to light, through an ethnography that searches beneath the layers of produced invisibility, are multiple social geographies, aggregative practices, forms of memory and claims to “wholeness” of - material and social – bodies, even in and for death; meaningful relationships that in the fragmented spaces of the margin, usually considered “non-places”, take shape.